Acute respiratory infection and its associated factors among children under-five years attending pediatrics ward at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia: institution-based cross-sectional study - Henok Dagne; Zewudu Andualem; Baye Dagnew; Asefa Adimasu Taddese (BMC, 2020)
Abstract Background Acute respiratory infection is manifested by cough accompanied by short rapid breathing which may be associated with death especially when there are other co-morbidities. From an estimated 5.4 million children under -five years that died in 2017-roughly half of those deaths occurred in sub-Saharan Africa and acute respiratory infection contributed to the highest number of deaths. The current study aimed at evaluating the prevalence of, and risk factors associated with, acute respiratory infection hospitalization in under-five years children hospitalized at the University of Gondar Comprehensive Specialized Hospital. Method An institution-based cross-sectional study was carried out from May 01/2019 to July 10/2019. After the selection of participants using simple random sampling, face to face interview was performed using a semi-structured pre-tested questionnaire. Data were also extracted from medical registration charts. We used EPI Info 7 for data entry and exported into SPSS 21 for analysis. Results were presented by simple frequency, percentage and mean for descriptive variables. Binary logistic regression analysis was used to test the association of covariates and outcome variable. Variables with a p < 0.2 during the bivariable binary logistic regression analysis were included in the multivariable logistic regression analysis. Variables with p < 0.05 were considered as significantly associated with acute respiratory infection. This study is reported following the Strengthening the Reporting of Observational Studies in Epidemiology guideline. Results Four hundred and twenty-two under-five years' children attending the Pediatrics ward were included in this study. The prevalence of acute respiratory infection among under-five years' children in this study was 27.3%. Children aged below 12 months (AOR:3.39, 95% CI: 1.19, 9.65), maternal age of 16 to 27 years (AOR: 1.95, 95% CI: 1.03, 3.70), maternal age of 28 to 33 years (AOR: 2.73, 95% CI: 1.40, 5.34), lack of maternal awareness of handwashing (AOR: 2.79, 95% CI: 1.15, 6.76), rural residence (AOR:2.27, 95% CI: 1.18, 4.39), and lack of meningitis (AOR: 0.22, 95% CI: 0.08, 0.55), were significantly associated with acute respiratory infection. Conclusion Acute respiratory infection was common among children under-five years. Child and maternal age, residence and maternal hand hygiene information were significant factors identified to be associated with an acute respiratory infection.